A novel heterogeneous superoxide support-coated catalyst for production of biodiesel from roasted and unroasted Sinapis arvensis seed oil - Hanif, Maryam; Bhatti, Haq Nawaz; Hanif, Muhammad Asif; Rashid, Umer; Hanif, Asma; Moser, Bryan R.; Alsalme, Ali (Multidisciplinary Digital Publishing Institute, 2021)
Disadvantages of biodiesel include consumption of edible oils for fuel production, generation of wastewater and inability to recycle catalysts during homogenously catalyzed transesterification. The aim of the current study was to utilize low-cost, inedible oil extracted from Sinapis arvensis seeds to produce biodiesel using a novel nano-composite superoxide heterogeneous catalyst. Sodium superoxide (NaO2) was synthesized by reaction of sodium nitrate with hydrogen peroxide via spray pyrolysis, followed by coating onto a composite support material prepared from silicon dioxide, potassium ferricyanide and granite. The roasted (110 °C, 20 min) and unroasted S. arvensis seeds were subjected to high vacuum fractional distillation to afford fractions (F1, F2 and F3) that correlated to molecular weight. For example, F1 was enriched in palmitic acid (76–79%), F2 was enriched in oleic acid (69%) and F3 was enriched in erucic acid (61%). These fractions, as well as pure unroasted and roasted S. arvensis seed oils, were then transesterified using NaO2/SiO2/PFC/Granite to give biodiesel a maximum yield of 98.4% and 99.2%, respectively. In contrast, yields using immobilized lipase catalyst were considerably lower (78–85%). Fuel properties such as acid value, cetane number, density, iodine value, pour point, and saponification value were within the ranges specified in the American biodiesel standard, ASTM D6751, where applicable. These results indicated that the nano-composite catalyst was excellent for production of biodiesel from unroasted and roasted S. arvensis seed oil and its fractions.